South Asia Nutrition Knowledge Initiative: Abstract digest April 2024 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
Welcome to the first edition of South Asia Nutrition Knowledge Initiative’s (SANI) Abstract Digest! In each issue, we aim to curate a selection of the latest and relevant studies on maternal and child nutrition for the South Asia region. We conduct literature search across peer-reviewed journals and identify studies of relevance. The abstracts in this document are reproduced in their original form from their source, and without editorial commentary about specific articles.